Epidemiological investigation and pathogenicity of Streptococcus suis in eastern China - Yang, Dehong; Xu, Jingyu; Hu, Meiling; Zhu, Jinmei; Ren, Baihua; Huang, Xianhui; Wang, Lianxiang (Frontiers in Microbiology, 2026)
Streptococcus suis (S. suis), a zoonotic gram-positive bacterium, is the etiological factor for septicemia and pneumonia in humans and pigs and poses a global public health threat. To date, epidemiological data from large-scale investigations of S. suis in swine populations across eastern China are still limited. This study investigated the serotypes, virulence genes, and pathogenicity of the isolates from 89 pig farms across 12 regions from 2022 to 2024. The overall infection and isolation rates were 59.59% (851/1728) and 16.1% (137/851), respectively. The infection rate was the highest in Guangdong Province (72.41%) (63/87) and the lowest in Hubei Province (43.75%) (7/16). Suckling piglets, nursery pigs, fattening pigs, and pregnant sows are susceptible to S. suis infection, with infection rates as high as 60%. The infection rates in spring, summer, autumn, and winter were 70.72% (215/304), 60.67% (344/567), 40.62% (132/325), and 68.97% (160/232), respectively. Serotype analysis of 137 isolates revealed increased serotype diversity in coastal provinces, especially in Guangdong, Jiangsu, and Shandong. Serotype 1 was detected in Liaoning. The most common serotype was serotype 2 (30.66%), especially in Guangdong, Guangxi, and Anhui, followed by serotype 7 (21.17%) and serotype 9 (10.95%). Virulence gene analysis revealed that the occurrence of gdh, gapdh, and orf2 (>89%) was high, whereas that of 89 k and epf was low (≤ 28.47%). Serotypes 1 and 7 frequently harbored mrp and gdh but often lacked 89 k and epf. Serotype 2 and serotype NT harbored all the tested genes, withlow 89 k occurrence rates. The occurrence rates of sly and epf (≤43.75%) werelow for serotype 9. Animal challenge experiments demonstrated that Serotype 2 induced acute death in Landrace pigs aged 42 days, with a mortality rate of 100%. In contrast, Serotype 7 was associated with low mortality rates (37.5%) and induced mild pathological symptoms, including pneumonia, myocarditis, and yellow effusion in the thoracic cavity. This study provides useful insights for the prevention and control of S. suis infection on pig farms in China.